ASPECTS OF SOCIAL RESPONSIBILITY AND SUSTAINABLE DEVELOPMENT OF THE CONSTRUCTION COMPANY - EMELIANOVA, Olena; TYTOK, Viktoriya; PYLYPCHUK, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article describes the main aspects of social responsibility and sustainable development of a construction company. It is noted that the social responsibility of construction enterprises is based on the concept of social responsibility, which is the responsible attitude of enterprises to their employees, consumers, partners and products they produce. It is noted that an important document regulating the main aspects of social responsibility of a construction company is the international standard ISO 26000, which takes into account the social requirements of the enterprise and serves as a guide to sustainable development. It was found that areas for improving the social responsibility of the construction business include improving equality and diversity, well-designed buildings and structures. Social responsibility should be at the heart of the construction business, reducing carbon emissions, reducing waste from construction projects, supporting local communities, and improving working conditions for employees. It is noted that in order to comply with the principles of sustainable development, construction companies should focus not only on profit, but also on key areas: people and the environment, since the main goals of sustainable construction are to minimize the depletion of natural resources, reduce greenhouse gas emissions and promote the well-being of both residents and surrounding communities. The advantages of sustainable development in the construction industry are highlighted. The importance of LEED certification is stated. The article characterizes the BREEAM building standard, which provides a basis for creating new building elements that are highly efficient and durable. It is noted that the sustainable development of a construction enterprise is regulated by the ISO 14001 standard "Environmental Management Systems. Requirements and Guidelines for Use", the main purpose of which is to minimize the harmful impact of the enterprise's production activities on the environment.
Keywords: construction industry; construction company; construction project; standard; certification; social responsibility; sustainable development; environmental friendliness